TURNOVER INTENTION IN MILLENNIAL GENERATION: THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK-LIFE BALANCE, AND PERCEIVED ORGANIZATIONAL SUPPORT - Romy, Elly; Biso, Hernansi; Hadikusumo, Reina A.; Sriharyati, Santy (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
Turnover intention, or the intention to leave an organization, has become a significant issue in the modern era, especially among the millennial generation, which has different work preferences from those of previous generations. This generation tends to value balance between personal and professional life and wants a work environment that supports personal development and well-being. This research aims to analyze the influence of transformational leadership, work-life balance and perceived organizational support on turnover intention in the millennial generation. This research uses a literature and field research design with a causal associative approach to see the relationship between several uncertain variables. The sample studied consisted of 150 respondents who were selected using purposive sampling. The results of the data analysis confirm that transformational leadership, work-life balance, and perceived organizational support have a positive and significant effect on turnover intention. This research will provide insight for organizations in designing effective management strategies to retain millennial employees. By understanding the influence of transformational leadership, work-life balance, and perceived organizational support on turnover intention, organizations can develop more adaptive and responsive policies to the millennial generation's needs, thereby reducing turnover rates and increasing team member retention.